Is attention deficit/hyperactivity disorder among men associated with initiation or escalation of substance use at 15‐month follow‐up? A longitudinal study involving young Swiss men. (26th May 2016) - Vogel, Tanja; Dom, Geert; van de Glind, Geurt; Studer, Joseph; Gmel, Gerhard; Strik, Werner; Moggi, Franz
Abstract: Background and Aims: Young adults with attention deficit/hyperactivity disorder (ADHD) show higher substance use disorder (SUD) prevalence relative to non‐ADHD controls; few longitudinal studies have examined the course of substance use with reference to conduct disorder (CD). We compared initiation and escalation of substance use at 15‐month follow‐up in men screened positive or negative for ADHD (ADHD + versus ADHD – ), controlling for CD presence in early adolescence. Design: Participants were recruited during August 2010 and November 2011 from the census of all young men who have to pass mandatory army conscription from three of six Swiss Army recruitment centres. A two‐wave data collection was performed via questionnaires at baseline and 15‐month follow‐up as a part of the longitudinal Cohort Study on Substance Use Risk Factors. Setting: Recruitment centres in Lausanne, Windisch and Mels, responsible for 21 cantons in German‐ and French‐speaking areas of Switzerland. Participants: Consecutive sample of 5103 male Swiss Army conscripts who provided informed consent and responded to questionnaires at baseline and 15‐month follow‐up. Their mean age was 20.0 (standard deviation = 1.21) years at baseline. Measurements: ADHD and CD were assessed using the adult ADHD Self‐Report Scale and the MINI International Neuropsychiatric Interview Plus, respectively, at baseline, and substance use was measured via self‐administered substance use questionnaires at baseline and follow‐up. Findings: Compared with the ADHD – group, the ADHD + group ( n = 215, 4.2%) showed heavier baseline substance use and increased likelihood of alcohol (χ 2 = 53.96; P < 0.001), tobacco (χ 2 = 21.73; P < 0.001) and cannabis use disorders (χ 2 = 48.43; P < 0.001). The extent of alcohol, tobacco and cannabis use in the two groups remained stable from baseline to follow‐up (no escalation). The ADHD + group was more likely to initiate substance use compared with the ADHD – group (higher initiation rates), particularly with amphetamines [odds ratio (OR) = 3.81; 95% confidence interval (CI) = 2.20–6.60; P < 0.001] and non‐medical use of ADHD medication (OR = 4.45; 95% CI = 2.06–9.60; P < 0.001). CD was associated with initiation of substance use but did not mediate the associations between ADHD and substance use, revealing that the impact of ADHD on substance use was independent of CD. Conclusions: For men in their early 20s, attention deficit/hyperactivity disorder is a risk factor for continued heavier but not escalating use of alcohol, tobacco and cannabis when already consuming these substances, compared with young men with no ADHD. It is also a risk factor for initiating the use of cannabis, stimulants, hallucinogens and sedatives, independent of conduct disorder in early adolescence.